Middle East respiratory syndrome coronavirus (MERS-CoV) infection: chest CT findings - Ajlan, Amr M; Ahyad, Rayan A; Jamjoom, Lamia Ghazi; Alharthy, Ahmed; Madani, Tariq A (American journal of roentgenology (1976), 2014)
The purpose of this study was to describe the chest CT findings in seven patients with Middle East respiratory syndrome coronavirus (MERS-CoV) infection. The most common CT finding in hospitalized patients with MERS-CoV infection is that of bilateral predominantly subpleural and basilar airspace changes, with more extensive ground-glass opacities than consolidation. The subpleural and peribronchovascular predilection of the abnormalities is suggestive of an organizing pneumonia pattern.